Case Report of a Unique Intra-Operative Finding in a Pediatric Distal Radius Non-Union: Does This Shed Light on Other Non-Unions or Malunions in Children? - Marius Negru; Adrian Emil Lazarescu; Corina Maria Stanciulescu; Liliana Catan; Calin Marius Popoiu; Eugen Sorin Boia (MDPI AG, 2024)
Non-unions are quite rare in closed fractures in children. Most distal radius fractures require orthopedic reduction and conservative treatment with very good radiological and clinical/functional results. In case of unsatisfactory reduction, surgical treatment is necessary to correct significant displacement. Surgical treatment consists of closed reduction and percutaneous fixation using K-wires. If closed reduction is not possible, open reduction and fixation is mandatory. Generally, fixation is obtained using K-wires, in most cases, even if open reduction is necessary, rarely locking plates, especially in adolescents. The present paper presents a case of non-union that eventually required open reduction and plating. During surgery, however, it became evident that the cause for non-union was the traumatic transposition of the long extensor radialis tendon, through the fracture site to the volar side of the distal forearm. The movement of the carpus translated to constant mobility in the fracture site, leading to non-union and a continuous tendency towards anterior angulation of the distal fragment. The tendon was reduced to its anatomical position, the fracture was reduced, and fixed using a locking plate, and union was achieved with no complications. Traumatic transpositions of tendons should be considered in pediatric non-unions, and restoring anatomy is essential.